2011
DOI: 10.1161/hypertensionaha.111.173203
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged Urocortin 2 Administration in Experimental Heart Failure

Abstract: Abstract-Although acute administration of urocortin 2 has beneficial actions in heart failure, the integrated hemodynamic, hormonal, and renal effects of sustained urocortin 2 treatment in this disease have not been investigated. In the current study, we administered a 4-day infusion of a vehicle control (0.9% saline; nϭ6) or urocortin 2 (0.75 g/kg per hour; nϭ6) to sheep with pacing-induced heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 30 publications
6
42
0
Order By: Relevance
“…Although the present study is the first report of the effects of UCn2 gene transfer on cardiac function, there have been several studies indicating favorable effects of UCn2 peptide infusion on the normal and failing heart in preclinical studies (Rademaker et al, 2002(Rademaker et al, , 2005(Rademaker et al, , 2011Davis et al, 2007a). UCn2 peptide infusion has also been used in clinical trials in heart failure (Davis et al, 2007b).…”
mentioning
confidence: 75%
See 2 more Smart Citations
“…Although the present study is the first report of the effects of UCn2 gene transfer on cardiac function, there have been several studies indicating favorable effects of UCn2 peptide infusion on the normal and failing heart in preclinical studies (Rademaker et al, 2002(Rademaker et al, , 2005(Rademaker et al, , 2011Davis et al, 2007a). UCn2 peptide infusion has also been used in clinical trials in heart failure (Davis et al, 2007b).…”
mentioning
confidence: 75%
“…Although UCn1 has been implicated in tissue permeability associated with lipopolysaccharide (LPS)-induced inflammation (Singh et al, 1999), UCn2, through selective CRFR2 activation, mediates protean beneficial effects including reduced renin-aldosterone activation, and is a potent inotrope with minimal effects on cardiac cyclic AMP (cAMP) (Bale et al, 2004). Peptide infusions of UCn2 in preclinical and clinical CHF have shown favorable effects on left ventricular (LV) function (Davis et al, 2007b;Rademaker et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have demonstrated that UCn2 gene transfer in normal mice has beneficial effects on LV contractile function through augmentation of Ca 2+ handling (5). The safety and efficacy of UCn2 peptide infusion has been confirmed in large-animal models of HF (19) and in patients with HF (4). A clinical HF study using infusion of an UCn2-related peptide, stresscopin, found similar results (7).…”
Section: Discussionmentioning
confidence: 99%
“…The discovery and development of more effective therapies is imperative. Intravenous delivery of an AAV vector encoding UCn2 provides numerous possible advantages over oral T2DM agents and insulin: (a) the insulin-sensitizing effect of UCn2 gene transfer would be anticipated to preserve β-cell function, a goal in the management of patients with early T2DM; (b) some oral T2DM agents, including thiazolidinediones, appear to be hazardous in patients with coronary artery disease or HF (23), but in contrast, UCn2 has beneficial effects on the heart (2,4,5,19,20); (c) repeated insulin injections or frequent oral medications are a nuisance for many patients -UCn2 gene transfer would circumvent this with a one-time treatment; (d) insulin and some oral T2DM agents are associated with weight gain, but in contrast, UCn2 gene transfer is associated with reduced weight gain in mice fed HFD ( Figure 7A); and (e) UCn2 gene transfer reduced fatty infiltration of the liver in both models of insulin resistance (Figures 7, B and C). Nonalcoholic fatty liver disease is a rapidly increasing problem, particularly among patients with T2DM and metabolic syndrome, and is a common cause for liver transplantation (24).…”
Section: Discussionmentioning
confidence: 99%